Significance of site‐specific radiation dose and technique for success of implant‐based prosthetic rehabilitation in irradiated head and neck cancer patients—A cohort study. (4th May 2021) - Wolf, Franziska; Spoerl, Steffen; Gottsauner, Maximilian; Klingelhöffer, Christoph; Spanier, Gerrit; Kolbeck, Carola; Reichert, Torsten E.; Hautmann, Matthias G.; Ettl, Tobias
Abstract: Background: Radiotherapy aggravates implant‐based prosthetic rehabilitation in patients with head and neck cancer. Purpose: To evaluate the impact of radiation dose at implant and parotid gland site for prosthetic rehabilitation. Material and methods: The retrospective study includes 121 irradiated head and neck cancer patients with 751 inserted implants. Radiation doses on implant bed and parotid gland site were recorded by 3‐dimensional modulated radiation plans. Implant success was clinically and radiographically evaluated according to modified Albrektsson criteria and compared to treatment‐ and patient‐specific data. Results: Implant overall survival after 5 years was 92.4% with an implant success rate of 74.9%. Main reasons for implant failure were marginal bone resorption (20.9%), implant not in situ or unloaded (9.6%) and peri‐implantitis (7.5%). A mean radiation dose of 62.6 Gy was applied with a mean parotid dose of 35 Gy. Modulating radiation techniques went along with lower grades of xerostomia ( p < 0.001). At implant site mean doses of 57.5, 42.0, and 32.3 Gy were recorded for oral, oropharyngeal, and hypopharyngeal/laryngeal carcinoma, respectively. Implant success inversely correlated to radiation dose at implant site. Strong predictors for implant failure in uni‐ and multivariate analysis were implant‐specific dose >50 Gy (HR 7.9), parotid dose >30 Gy (HR 2.3), bone (HR 14.5) and soft tissue (HR 4.5) transplants, bad oral hygiene (HR 3.8), nonmodulated radiation treatment planning (HR 14.5), and nontelescopic prosthetics (HR 5.2). Conclusion: Radiotherapy impedes implant success in a dose‐dependent manner at implant site. Modern radiation techniques effectively reduce xerostomia favoring implant‐based prosthetic rehabilitation. Implantation in bone grafts is more critical and telescopic‐retained overdentures should be preferred.